Correlative light and electron microscopy II - Müller-Reichert, Thomas; Verkade, Paul (Methods in cell biology, 2014)
This new volume of Methods in Cell Biology looks at methods for analyzing correlative light and electron microscopy (CLEM). With CLEM, people try to combine the advantages of both worlds, i.e. the dynamics information obtained by light microscopy and the ultrastructure as provided by electron microscopy. This volume contains the latest techniques on correlative microscopy showing that combining two imaging modalities provides more than each technique alone. Most importantly it includes the essential protocols, including tips, tricks and images for you to repeat these exciting techniques in you